2006
DOI: 10.1167/iovs.06-0318
|View full text |Cite
|
Sign up to set email alerts
|

Protection of RPE Cells from Oxidative Injury by 15-Deoxy-Δ12,14-Prostaglandin J2by Augmenting GSH and Activating MAPK

Abstract: Independent of its PPARgamma activity, dPGJ(2) protected cells from oxidative stress by elevating GSH and enhancing MAPK activation. Thus, dPGJ(2) may delay the development of dry-type age-related macular degeneration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
58
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 57 publications
(61 citation statements)
references
References 41 publications
3
58
0
Order By: Relevance
“…The sensitivity of cardiac myocytes to hydrogen peroxide was increased in MEKK1-negative cells (upstream of JNK), further suggesting the anti-apoptotic role of the JNK pathway (22). It has also been shown that the protective effect of cyclopentenone 15-deoxy-D12,14-prostaglandin J2 (dPGJ2), an endogenous PPARγ agonist that protects RPE cells from oxidative injury, is dependent on the activation of JNK and p38 (23). Thus, the JNK pathway is not simply a pro-or an anti-apoptotic pathway, which depends on cell and stimulus type, but requires co-activation of additional pathways and is also dependent on the duration of activation.…”
Section: Discussionmentioning
confidence: 99%
“…The sensitivity of cardiac myocytes to hydrogen peroxide was increased in MEKK1-negative cells (upstream of JNK), further suggesting the anti-apoptotic role of the JNK pathway (22). It has also been shown that the protective effect of cyclopentenone 15-deoxy-D12,14-prostaglandin J2 (dPGJ2), an endogenous PPARγ agonist that protects RPE cells from oxidative injury, is dependent on the activation of JNK and p38 (23). Thus, the JNK pathway is not simply a pro-or an anti-apoptotic pathway, which depends on cell and stimulus type, but requires co-activation of additional pathways and is also dependent on the duration of activation.…”
Section: Discussionmentioning
confidence: 99%
“…Given the central role RPE plays in AMD pathogenesis, a commonly used experimental model to study the link between oxidative stress and AMD involves the use of cultured human RPE (ARPE-19) cells. Common endpoints include cell survival, morphology, activation of signaling cascades, and cytokine production (Chan et al, 2008;Dong et al, 2011;Glotin et al, 2006;Jiang et al, 2009;Klettner and Roider, 2009;Qin et al, 2006;Tsao et al, 2006;Wang et al, 1998;Wu et al, 2010).…”
Section: Age-related Macular Degenerationmentioning
confidence: 99%
“…In response to oxidants such as hydrogen peroxide or tert-butyl hydroperoxide, MAPK (most notably ERKs and p38 MAPK) activation has been shown to either protect against or exacerbate oxidative injury, differentiated by the amount of RPE cell death (Chan et al, 2008;Dong et al, 2011;Glotin et al, 2006;Jiang et al, 2009;Klettner and Roider, 2009;Qin et al, 2006;Tsao et al, 2006;Wang et al, 1998;Wu et al, 2010). These findings also raise questions as to the impact of oxidative stress on the outer BRB when the MAPK pathway is modulated pharmacologically by a MEK inhibitor.…”
Section: Mapk Activation and Oxidative Stress Response In The Retinamentioning
confidence: 99%
“…15d-PGJ2 possesses anti-inflammatory properties, and plays a protective role against oxidative stress both in vitro and in vivo (Giri et al, 2004;Itoh et al, 2004;Qin et al, 2006). Several studies have shown that 15d-PGJ2 affects the Nrf2-mediated transcription pathway.…”
Section: Introductionmentioning
confidence: 99%